Qualitative Analysis Of The Learning Process At Krapyak Wetan State Elementary School - Hidayah, Safitri Nurul; Septikasari, Zela (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to gain a deeper understanding of the dynamics of individual variation in the learning process at Krapyak Wetan Public Elementary School, Bantul, Yogyakarta Special Region. The main focus of this study is to examine how differences in student characteristics influence the effectiveness of classroom learning. The individual variations observed include aspects of intelligence, learning styles, personality, and temperament, which in practice have proven to be important factors in determining the success of the learning process. This study used a descriptive qualitative approach with data collection techniques such as participatory observation, in-depth interviews, and documentation. The research subjects included the principal, grade I, II, and III teachers, and students in the 2024/2025 academic year as the primary data sources. The results show that Krapyak Wetan Public Elementary School has consistently implemented the Independent Curriculum through the application of differentiated learning. This approach allows teachers to adapt learning strategies to the needs, potential, and characteristics of each student. In its implementation, teachers use various adaptive methods, such as the use of visual, auditory, and kinesthetic media to accommodate the diversity of student learning styles. Furthermore, learning is supported by peer tutoring strategies, project-based learning, and flexible grouping, encouraging interaction and collaboration among students. The evaluation process is carried out continuously through formative and summative assessments tailored to each individual's development. This demonstrates the school's awareness and systematic efforts to create more inclusive and responsive learning.